Soemmering’s Ring in a spontaneous partially absorbed lens: a case report - Mohammad Salmi, Muhammad Syamil; Mahmud, Mazaya; Razali, Amirah; Md Salleh, Rafidah (Cureus inc, 2022)
Soemmering's ring and spontaneous lens absorption are two distinct conditions that are uncommon and unlikely to occur simultaneously. We report a case of a 67-year-old man who presented with blurred vision in his left eye and has had poor eyesight since birth. His right and left eye visual acuities were 6/7.5 and hand movement (HM), respectively. There was no relative afferent pupillary defect (RAPD). The right eye’s examination was unremarkable. The left eye revealed a spontaneous rupture of the anterior lens capsule with partially absorbed lens material and the presence of Soemmering's ring. There was no evidence of phacodonesis. The left fundus appeared slightly hazy, while the retina appeared flat. Extraction of the left eye lens was performed for the patient, and he was left aphakic.